Blockchain in the Lens of Populism : A Short Communication of Research Evidence - Sharma, Aarti Mehta; Sethi, Madhvi; Vidyasagar, A.; Ravichandran, Sabari Shankar (Prabandhan: Indian Journal of Management, 2024)
Purpose : Blockchains are a sophisticated and extensively utilized technology that facilitates bulk data management operations and increases productivity for many companies, including governments. However, because of the high prices and complexity, not all large firms could take advantage of this disruptive weapon, which leads to populist ideas. The purpose of this brief message was to examine the new, popular ideas in blockchain technology that improve the global productive efficiencies of businesses. Methodology : The two-stage method that produced the insights in this communication was followed by a sentiment analysis, network map, theme map, and latent Dirichlet allocation. Findings : Blockchain technology has been widely adopted by the majority of the major services businesses. The industries that are currently scaling up, however, lack the viability to use this technology. The results also showed that neither academic research nor the corporate framework had examined the new populism situation. Practical Implications : The productive efficiency of industries would be improved if governments and policymakers used populistic settings in blockchain technology. Additionally, eliminating the cost-based inequalities would inspire populist ideas throughout all industries, generating combined revenues. Originality/Value : This brief message implied negative opinions about blockchain technology and was taken from a significant study on the impact of this technology on business success. This message is meant to benefit not only corporations but also governments and policymakers in facilitating regular access to technology for expanding industries that could strengthen economies.